Impact of hysteroscopy on reproductive outcomes in patients with recurrent implantation failure - Sa, Le Viet Nguyen; Xuan, Nguyen Thanh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2026)
Background: Hysteroscopy is considered the gold standard for diagnosing intrauterine abnormalities and allows simultaneous management. However, its role in improving outcomes in patients with recurrent implantation failure (RIF) remains controversial. This study aimed to describe hysteroscopic findings and and to evaluate reproductive outcomes following surgical intervention in these patients. Methods: This prospective study included 41 women with RIF at the Center for Assisted Reproduction, Hue Central Hospital, from March 2025 to March 2026. Diagnostic and operative hysteroscopy was performed during the follicular phase of the menstrual cycle (day 6–10). Patients subsequently underwent embryo transfer cycle. Results: The mean age of the study population was 33.6 ± 4.6 years, with an average of 2.2 ± 0.5 previous failed embryo transfers, with most patients having two failed transfers (78.1%). Intrauterine abnormalities were detected in 78.1% of cases. The most common lesions included endometrial polyps (58.5%), chronic endometritis (29.3%), and micropolyps (17.1%), followed by submucosal fibroids, cesarean scar defects, and uterine anomalies. The biochemical, clinical and on going pregnancy rate was 61.3%, 51.6%, and 45.2%, respectively. Although pregnancy outcomes were higher after hysteroscopic intervention, the differences were not statistically significant (p > 0.05). Conclusion: Hysteroscopy may be a valuable tool for both diagnosis and treatment of intrauterine abnormalities in patients with RIF, with a trend toward improved reproductive outcomes. Larger controlled studies are needed to confirm these findings